2015
DOI: 10.1038/srep15199
|View full text |Cite
|
Sign up to set email alerts
|

De novo KCNB1 mutations in infantile epilepsy inhibit repetitive neuronal firing

Abstract: The voltage-gated Kv2.1 potassium channel encoded by KCNB1 produces the major delayed rectifier potassium current in pyramidal neurons. Recently, de novo heterozygous missense KCNB1 mutations have been identified in three patients with epileptic encephalopathy and a patient with neurodevelopmental disorder. However, the frequency of KCNB1 mutations in infantile epileptic patients and their effects on neuronal activity are yet unknown. We searched whole exome sequencing data of a total of 437 patients with infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 42 publications
9
111
0
Order By: Relevance
“…The protein forms a functional tetramer, where each subunit is comprised of six membrane-spanning alpha helices (S1–S6), with (S1–S4) involved in voltage sensing segments and (S5–S6) forming a central pore with a voltage-dependent gating hinge that opens and closes the channel as a function of voltage. Mutations in KCNB1 have an established role in epileptic encephalopathy and previous studies (Epi4K Consortium et al 2013; Torkamani et al 2014; Saitsu et al 2015) have found six de novo causative mutations: three in the S5–S6 linker and one each in the S4, S5 and S6 helices (Figure 9a). All are predicted deleterious by SNP3D profile (Yue and Moult 2006).…”
Section: Resultsmentioning
confidence: 90%
“…The protein forms a functional tetramer, where each subunit is comprised of six membrane-spanning alpha helices (S1–S6), with (S1–S4) involved in voltage sensing segments and (S5–S6) forming a central pore with a voltage-dependent gating hinge that opens and closes the channel as a function of voltage. Mutations in KCNB1 have an established role in epileptic encephalopathy and previous studies (Epi4K Consortium et al 2013; Torkamani et al 2014; Saitsu et al 2015) have found six de novo causative mutations: three in the S5–S6 linker and one each in the S4, S5 and S6 helices (Figure 9a). All are predicted deleterious by SNP3D profile (Yue and Moult 2006).…”
Section: Resultsmentioning
confidence: 90%
“…Among them, using the 95‐genes panel, we uncovered mutations in these genes in three patients whose phenotype was concordant with previously published probands for KCNQ2 and KCNT1 , whereas the child harboring the KCNB1 mutation exhibited West syndrome. There are only seven patients reported to carry missense mutations in this gene and three of them presented infantile spasms [Torkamani et al., , Saitsu et al., ; Allen et al., ]. The patient carrying the KCNA2 variant exhibited late infantile drug‐resistant seizures followed by a good outcome with seizure‐freedom in childhood, confirming the spectrum of KCNA2 ‐related phenotypes from early and severe infantile EE to mild epilepsy with good outcome [Syrbe et al., ].…”
Section: Discussionmentioning
confidence: 87%
“…Developmental regression can occur in early childhood [21, 22]. In some cases, patients demonstrate behavioral abnormalities, like autistic features [23], stereotyped hand-wringing [24], hyperactivity, irritability, agitation, and aggression [25]. There are no previous reports linking KCNB1 variants to a RTT-like presentation.…”
Section: Discussionmentioning
confidence: 99%